Analysis of the Influence of Service Quality at Patient Registration Sites on Patient Satisfaction at the Singosari Health Center - Rusdi, Achmad Jaelani; Ikawati, Fita Rusdian; Kusumaningrum, Tyas (PROMOTOR, 2025)
This study aims to analyze the effect of the quality of patient registration services on patient satisfaction at the Singosari Health Center. This study uses a quantitative method with an observational analytical approach and a cross-sectional design. The research sample was outpatients who had received services at the Singosari Health Center calculated using the Slovin formula with a total of 98 respondents selected using random sampling techniques. The data was collected using questionnaires and analyzed using the Spearman statistical test. The research results from the Spearman Rank Test obtained a p-value of 0.000 (p<0.05), and Ho was rejected and declared to be related. It shows that there is a significant relationship between the quality of service at the patient registration site and patient satisfaction at the Singosari Health Center. The dimensions of service quality which include tangibles, reliability, responsiveness, assurance, and empathy affect patient satisfaction. The better the quality of service provided, the higher the level of patient satisfaction.